2018
DOI: 10.1002/jcp.26839
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferation–activated receptor‐γ inhibits transforming growth factor‐β1‐induced airway smooth muscle cell proliferation by suppressing Smad–miR‐21 signaling

Abstract: The aims of the current study were to examine the signaling mechanisms for transforming growth factor-β1 (TGF-β1)-induced rat airway smooth muscle cell (ASMC) proliferation and to determine the effect of activation of peroxisome proliferation-activated receptor-γ (PPAR-γ) on TGF-β1-induced rat ASMC proliferation and its underlying mechanisms. TGF-β1 upregulated microRNA 21 (miR-21) expression by activating Smad2/3, and this in turn downregulated forkhead box O1 (FOXO1) mRNA expression. In addition, TGF-β1-Smad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…On the other hand, HGFs cultured on Zn-Ti had the highest proliferation rate and amount among all groups. Since Smad2 and Smad3 were closely related to cell proliferation, the relatively higher expression of them in HGFs on Zn-Ti than other groups, especially Mg&Zn-Ti whose Zn 2+ release was lower than Zn-Ti, indicated that Zn 2+ might be a main reason in regulating HGFs proliferation [ 65 , 66 ]. It was reported that the function and homeostasis of Zn in cells or organisms were mainly controlled by Zn transporters [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, HGFs cultured on Zn-Ti had the highest proliferation rate and amount among all groups. Since Smad2 and Smad3 were closely related to cell proliferation, the relatively higher expression of them in HGFs on Zn-Ti than other groups, especially Mg&Zn-Ti whose Zn 2+ release was lower than Zn-Ti, indicated that Zn 2+ might be a main reason in regulating HGFs proliferation [ 65 , 66 ]. It was reported that the function and homeostasis of Zn in cells or organisms were mainly controlled by Zn transporters [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of PPARγ activation in the resolution of pneumonia has been confirmed by experimental studies [42,67,68]. A decrease in the proliferation of smooth muscle cells of airways in rats upon the activation of PPARγ was observed [69]. Lakshmi et al have shown that the PPARγ deficiency contributes to the development of airway hyperresponsiveness, bronchial remodeling, and the inhibition of MUC5AC activity [70].…”
Section: Ppar-dependent Mechanisms In Asthmamentioning
confidence: 91%
“…TGF-β1 has been reported to be elevated and involved in airway remodeling or shortening in patients with asthma [19]. A recent study revealed that introduction of TGF-β1 facilitates proliferation of bronchial epithelial cells and smooth muscle cells in asthma [20,21]. Since TGF-β1 opens up the possibility of cell proliferation, we hypothesized TGF-β1 is required for miR-744-mediated progression in severe asthma.…”
Section: Introductionmentioning
confidence: 99%